(untitled) (Conference Zone, 2022)
In this article, we will talk about the very rapid development of computer graphics, wide use of graphics programs, three types of computer graphics, classes of programs that work with computer graphics, raster packages, digital video applications, special computer programs, the development of information in graphic form